Effect of sawdust filler with Kevlar/basalt fiber on the mechanical properties epoxy–based polymer composite materials. (2023) - Ramesh, V.; Karthik, K.; Arunkumar, K.; Unnam, Neethish Kumar; Ganesh, R.; Rajkumar, C.
Abstract: In this paper aim to design and develop the new hybrid composite material high-strength lightweight and high-strength mat fibers fabricated from natural fibers has increased tremendously. The use of natural fibers has rapidly increased due to their high availability, low density, and renewable capability over synthetic fiber. The materials used to fabricate hybrid composite laminates are Basalt/Kevlar fiber with Sawdust particles mixed with Epoxy LY556 resin, the ratio was fixed 50:50 between the reinforcement and matrix material. Compression molding techniques were used for fabricating laminates, followed by six different sample laminates with changing the stacking sequence to seven layers. After curing laminates as per the ASTM standard followed for mechanical properties to perform the experiments, surface analysis microstructure study also carryout, the high tensile strength of 328 MPa, Flexural strength of 380 MPa, Impact strength 13 MPa, which used for automotive (4 Wheelers) the interior part may be replaced with existing materials.